Axisymmetric open magnetic systems for plasma confinement - Kruglyakov, E.P.; Dimov, G.I.; Ivanov, A.A.; Koidan, V.S. (Вопросы атомной науки и техники, 2002)
At present, three modern types of different mirror machines for plasma confinement and heating exist in Novosibirsk (Gas Dynamic Trap, -GDT, Multi-mirror, - GOL-3, Tandem Mirror, -AMBAL-M). All these systems are attractive from the engineering point of view because of very simple axisymmetric geometry of magnetic configurations. In this paper, the status of different confinement systems is presented. The experiments most crucial for the mirror concept are described such as a demonstration of different principles of suppression of electron heat conductivity (GDT, GOL-3), finding of MHD stable regimes of plasma confinement in axisymmetric geometric of magnetic field (GDT, AMBAL-M), an effective heating of dense plasma by relativistic electron beam (GOL-3), observation of radial diffusion of quiescent plasma with practically classical diffusion coefficient (AMBAL-M), etc. The main plasma parameters achieved in mentioned above systems are presented.